2018
DOI: 10.1186/s40634-018-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dynamic change in regenerated tendons in a mouse model

Abstract: BackgroundUsing the film model method, the process whereby a substance called tendon gel is secreted from transected tendon ends and changed into a tendon after application of a traction force is known. The objective of this study was to investigate the association between mechanical properties in the early stages of tendon regeneration and time by using the film model method.MethodAdult male ddY mice, closed colony mice established and maintained in Japan, were prepared for each experimental group. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We attributed this result to the completion of the connecting junctions between the tendon parenchyma and tendon gel after the fth day in many tendon gels. Consequently, the contraction of the gastrocnemius exerted traction stress on the tendon gel, which was thought to promote morphological changes in the tenocytes and collagen maturation, as revealed by Torigoe et al [11] and Ohashi et al [13] using murine models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We attributed this result to the completion of the connecting junctions between the tendon parenchyma and tendon gel after the fth day in many tendon gels. Consequently, the contraction of the gastrocnemius exerted traction stress on the tendon gel, which was thought to promote morphological changes in the tenocytes and collagen maturation, as revealed by Torigoe et al [11] and Ohashi et al [13] using murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tendons generally contain only a few at tenocytes [22,23], but in the gels of D3 and D5 observed in this study, many round cells-also considered tenocytes-were actually observed. According to the research by Ohashi et al [13] with murine models, tenocytes were generated at the edges of the tendon in the early stage; subsequently, they were spread throughout the gel and their shape was changed from round to at, indicating maturation. These ndings are similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, D3 and D5 gels contained many round tenocytes. Ohashi et al reported that [ 23 ] tenocytes in the murine models were generated at the tendon edges during the early stage, spreading throughout the gel, and their shapes changed from round to flat, indicating in vivo maturation. We observed a histologically significant difference between D3/D5 and D10/D15 gels before the tensile process, which was because of the completion of connecting junctions between the tendon parenchyma and tendon gel.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that a translucent gel-like substance—called tendon gel —was secreted from the cut tendon stump and it was a key material for tendon regeneration [ 31 ]; in addition, maturation of tendon gel induced by the application of mechanical stress was observed via electron microscopy [ 31 ]. Similarly, Ohashi et al [ 23 ] reported that tendon gel matures physiologically and histologically under traction; moreover, an appropriate in vivo preservation period is needed for optimal traction-induced tendon gel maturation in murine models. These results support other previous reports showing the importance of applying mechanical force for the regeneration of injured tendons [ 12 , 34 ].…”
Section: Introductionmentioning
confidence: 99%